Evaluation and optimization of machining performance for rotary ultrasonic machining of Al/SiC composite material. (October 2019) - Kumar, Jatinder
Abstract: In manufacturing industries, Al/SiC composite material is highly demanded due to its excellent properties. However, the difficulties in its machining restrict the application and competitiveness of this material. This investigation is aimed at studying the impact of different experimental conditions (feed rate, spindle speed, and ultrasonic power) on responses of interest (material removal rate, surface roughness, and chipping thickness) in rotary ultrasonic machining of Al/SiC composite material. The experiments have been planned by using full factorial design. Analysis of variance (ANOVA) is also employed to identify the significant factors and the optimized process settings for the different responses. The experimental results showed that feed rate was the most significant factor for material removal rate and surface roughness. However, all the factors were found to be insignificant for chipping thickness. From the surface topography analysis of the machined surface, no surface damage in the form of micro-cracks etc. was visible.